Experimental investigation on corroded cold-formed steel beam-columns under compression and major axis bending. (June 2020) - Nie, Biao; Xu, Shanhua; Zhang, Zongxing; Gu, Renjun
Abstract: This paper presents the results of the experimental and finite element study that was performed to analyze the buckling behavior of corroded cold-formed steel beam-columns. Six specimens with different corrosion degrees were tested under compression and major axis bending. The residual thickness distribution and the mechanical properties of the corroded specimens were analyzed. A nonlinear finite element model predicting the buckling behavior of corroded cold-formed steel beam-columns was proposed. Finally, the influence of the parameters on ultimate load and failure mode were discussed, and the parameters include the parts, locations and lengths of the corroded region. The results indicated that when the thickness loss ratio was below 0.467, the decrease of the corrosion reduction factor for the elastic modulus was small, and then accelerated obviously. The corrosion reduction factor for the yield strength decreased linearly as the thickness loss ratio increased. Local buckling of the web of the corroded specimens was easier to occur than the web of the non-corroded specimen. The corrosion reduction factor for the ultimate load mainly depended on the minimum thickness of the cross-section. The flange corrosion most significantly affected the bearing capacity of the cold-formed steel beam-columns with localized corrosion. The locations and length of the corroded region has a little effect on the ultimate load and failure mode of corroded cold-formed steel beam-columns. Highlights: The buckling behavior of the corroded cold-formed steel beam-columns were analyzed. A finite element model for corroded cold-formed steel beam-columns was established. The influence of the parameters (the parts, locations and lengths of the corrosion region)on ultimate load and failure mode were discussed.